Geriatrische Notfallpatienten: Qualität in der notfallmedizinischen Versorgung - Schuster, S.; Singler, Katrin; Dormann, Harald (Notfall und Rettungsmedizin, 2016)
The number of geriatric patients in emergency departments is steadily increasing. These patients often present in the emergency departments with complex and time sensitive diseases, which represent a particular challenge for emergency physicians and nurses. Despite this fact, there were no generally accepted quality indicators for geriatric emergency care in Germany available. To address this deficit, an interdisciplinary committee of emergency physicians and nurses, and other experts in emergency medicine and health economics developed a set of 69 quality indicators for the emergency care of geriatric patients (GeriQ-ED©) according to the scientific methodology of QUALIFY. In addition, the European Task Force on Geriatric Emergency Medicine (ETFGEM) developed a European Curriculum of Geriatric Emergency Medicine (ECGEM). Therefore, now we have a good basis in order to close the lack of knowledge in physician and nurses education to improve the outcome of geriatric patients in emergency departments.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Emergency care; Emergency department; GeriQ-ED; QUALIFY; Quality